2004
DOI: 10.5713/ajas.2004.588
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Porcine Adiponectin and Stearoyl Coenzyme a Desaturase Genes in Differentiating Adipocytes

Abstract: The gene expression of porcine adiponectin and stearoyl coenzyme A desaturase (SCD) was investigated in this study.The partial gene sequences for adiponectin and SCD were amplified by RT-PCR from subcutaneous adipose tissue and cloned by TA cloning techniques. Sequences of these genes were determined and found to be highly homologous to that of other species, suggesting similar function of these genes as in other species. The transcripts of these adipocyte-related genes in pig tissues were measured by Northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
(33 reference statements)
1
11
0
1
Order By: Relevance
“…The membrane was prehybridized at 42°C in UltraHyb (Ambion) for 1 h, and then the denatured cDNA probe (95°C for 5 min) was added at a concentration of 1 pM to hybridize with the targeted gene transcripts overnight at 42°C. The porcine 18S sequence was previously described (Wang et al, 2004), and other probe sequences are indicated in Table 1. Primers used to synthesize the probes for 18s, decorin, adipocyte (A−) fatty acid binding protein (FABP), and lactate dehydrogenase B subunit (LDH-B) are also in Table 1.…”
Section: Northern Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The membrane was prehybridized at 42°C in UltraHyb (Ambion) for 1 h, and then the denatured cDNA probe (95°C for 5 min) was added at a concentration of 1 pM to hybridize with the targeted gene transcripts overnight at 42°C. The porcine 18S sequence was previously described (Wang et al, 2004), and other probe sequences are indicated in Table 1. Primers used to synthesize the probes for 18s, decorin, adipocyte (A−) fatty acid binding protein (FABP), and lactate dehydrogenase B subunit (LDH-B) are also in Table 1.…”
Section: Northern Analysismentioning
confidence: 99%
“…Recent research indicates that adipose tissue is also an endocrine tissue that secretes leptin, adiponectin, and other factors into the blood to regulate energy homeostasis (Mohamed-Ali et al, 1998;Havel, 2002). Porcine adipose tissue has abundant mRNA for adiponectin mRNA and its receptors (Ding et al, 2004;Wang et al, 2004) and produces leptin (Ramsay et al, 1998). These findings indicate that the adipose tissue in pigs also acts as an endocrine tissue and expresses genes involved in regulating metabolism and physiological functions in other tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian adiponectin genes that contain three exons and two introns are highly conserved between species (Hu et al 1996). For example, the homology between pig and mouse, rat and dog was 83, 82 and 90% respectively (Wang et al 2004). The shorter globular adiponectin (g AdipoQ) possesses potent biological activities that have similar properties to full AdipoQ.…”
Section: R216mentioning
confidence: 99%
“…Previous research was conducted to investigate the regulation of adiponectin and AdipoR expression in liver and skeletal muscle tissue [8][9][10]. Li et al (2005) found that AdipoR1 is widely distributed in various tissues of normal Wistar rats, with the highest expression detected in the testis and skeletal muscle [11].…”
Section: Elisa Analysis Of Adiponectinmentioning
confidence: 99%